QUANTUM MATHEMATICS: BACKGROUNDS AND SOME APPLICATIONS TO NONLINEAR DYNAMICAL SYSTEMS - Bogolyubov, N. N., Jr.; Golenia, J.; Prykarpatsky, A. K.; Taneri, U. (Springer, 2008)
The backgrounds of quantum mathematics, a new discipline in mathematical physics, are discussed and analyzed from both historical and analytical points of view. The magic properties of the second quantization method, invented by Fock in 1934, are demonstrated, and an impressive application to the theory of nonlinear dynamical systems is considered.
Keywords: Hilbert-Space Approach; Differential-Equations; 1St Integrals; Symmetries; Computers